2017
DOI: 10.1037/gpr0000111
|View full text |Cite
|
Sign up to set email alerts
|

How Gullible are We? A Review of the Evidence from Psychology and Social Science

Abstract: A long tradition of scholarship, from ancient Greece to Marxism or some contemporary social psychology, portrays humans as strongly gullible—wont to accept harmful messages by being unduly deferent. However, if humans are reasonably well adapted, they should not be strongly gullible: they should be vigilant toward communicated information. Evidence from experimental psychology reveals that humans are equipped with well-functioning mechanisms of epistemic vigilance. They check the plausibility of messages again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 177 publications
(190 reference statements)
2
89
0
1
Order By: Relevance
“…For example, it appears as though classification depends upon some possibly-unattainable normative criterion: Taber and Lodge (2006) lament that determining whether the influence of specific prior beliefs is "rational" skepticism or "irrational" bias is a "critical normative question," "but one that empirical research may not be able to address" (p. 768), because normative questions lie outside the purview of science. Added to this ambiguity, the human tendency to be skeptical of information that is incoherent with prior beliefs is plausibly explained by alternative motivations, such as to avoid being too easily manipulated into holding false or otherwise-costly beliefs by other people (Mercier, 2017(Mercier, , 2020.…”
Section: Considering Alternative Interpretations Of Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it appears as though classification depends upon some possibly-unattainable normative criterion: Taber and Lodge (2006) lament that determining whether the influence of specific prior beliefs is "rational" skepticism or "irrational" bias is a "critical normative question," "but one that empirical research may not be able to address" (p. 768), because normative questions lie outside the purview of science. Added to this ambiguity, the human tendency to be skeptical of information that is incoherent with prior beliefs is plausibly explained by alternative motivations, such as to avoid being too easily manipulated into holding false or otherwise-costly beliefs by other people (Mercier, 2017(Mercier, , 2020.…”
Section: Considering Alternative Interpretations Of Our Resultsmentioning
confidence: 99%
“…Such evidence implies that the tendency for reasoning to be affected by the coherence between new information and specific prior beliefs is a feature of human psychology that is independent of the motivation to reach conclusions congenial to political group identity. Indeed, this seemingly general human tendency is well captured by other theoretical frameworks-such as the theory of "epistemic vigilance," which argues that skepticism of new information that is incoherent (versus coherent) with prior beliefs forms part of a suite of adaptive cognitive mechanisms that guard against individuals being too easily manipulated into holding false or otherwise-costly beliefs by other people (Mercier, 2017(Mercier, , 2020Sperber et al, 2010).…”
Section: Why Prior Beliefs Undermine Inferences Of Politically Motivamentioning
confidence: 99%
“…Before reviewing the experimental literature looking at whether people take these cues into account, we must specify that majority rules are only one of the factors deciding how much weight people give to others' opinions: people also look at the content of the opinion and of the arguments supporting it (for reviews, see Mercier 2017;Sperber et al 2010). In some cases, these other factors trump majority rules, as when the correct answer to a logical problem is defended by only one individual against many individuals agreeing on the incorrect answer.…”
Section: When Should Majority Rules Be Followed?mentioning
confidence: 99%
“…Communication is particularly risky for humans, given its importance in their ecology. As a result, it has been suggested that humans have been endowed with cognitive mechanisms whose function is to evaluate communicated information (Mercier 2017;Sperber et al 2010). These mechanisms of epistemic vigilance would take into account a variety of cues and influence which messages we accept and which we reject.…”
Section: Conclusion: Making Sense Of Divergent Findingsmentioning
confidence: 99%
“…While the FFABB supports belief-default models, it also implies a quick rejection of information inconsistent with extant mental beliefs. Although there is some confusion in the literature on this point (Mercier, 2017;Richter et al, 2009;Sperber et al, 2010), belief-default models are not mutually exclusive with fast and efficient epistemic vigilance perspectives 25 .…”
Section: Discussionmentioning
confidence: 99%